Characterization of in situ ruminal degradabilty of dry matter in new varieties of drought tolerant Cenchrus purpureus - Ledea, J. L.; La O, Oreste; Ray, J. V. (Cuban Journal of Agricultural Science, 2016)
Two Creole cows, 450 ± 10 kg live weight, cannulated in rumen were used, with the purpose of studying the kinetics of in situ ruminal degradability of dry matter of leaves and stems of new varieties of drought tolerant Cenchrus purpureus (CT-601, CT-603 and CT-605) obtained by tissue culture at different regrowth ages (60, 80, 100 and 120 d).For that, they were introduced in duplicate bags in the rumen for 0, 4, 6, 8, 12, 24, 48 and 72 h. The results of the ruminal fermentation were fitted to the exponential equation (a + b) *(1-eˆ(-c*t)). For ages 60, 80 and 100 d, the CT-603 had the highest degradability of the potentially degradable fraction (a + b) of the leaves dry matter, with 81.2, 97.8 and 77.5 %, respectively. For 120 d, was the CT-605 which showed better performance of this fraction, with 84.7%. For the stems, at 60 d, the CT-605 showed 94.6% degradation of the fraction a + b, while the CT-601 and CT-603, at 80 d, showed values of this fraction of 75.2 and 75.1 %, respectively. For 100 and 120 d, CT-601 and CT-603, with 59.7 and 88.8 %, respectively, were highlighted. The protein tenors began to decrease below 7% from 80 d of regrowth. For DM degradability in leaves and stems, each variety showed values that exceeded 50% degradation. It is recommended using the ages of 80 and 100 d, in both botanical fractions, to supply ruminants. Key words: Cenchrus purpureus, ruminal degradability, Pennisetum purpureum, botanical fractions